Expanding graceful trees - I Nengah Suparta; I Dewa M. Agus Ariawan (Electronic Journal of Graph Theory and Applications (EJGTA), 2020)
Two methods for expanding graceful trees are introduced. In constructing a larger graceful trees, these methods are based on a collection of certain graceful trees and one graceful tree as the core of the produced graceful tree.